2018
DOI: 10.1007/s00167-018-5175-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional measurement misidentifies alignment outliers in total knee arthroplasty: a comparison of two- and three-dimensional measurements

Abstract: Purpose Two-dimensional (2D) and three-dimensional (3D) measurements of prosthetic alignment and "outliers" after total knee arthroplasty (TKA) might not necessarily be comparable. The aim of this study was to compare the use of 2D and 3D measurements in the identiication of prosthetic alignment and outliers after TKA. Methods This cross-sectional study included 159 consecutive TKAs. All patients underwent plain radiography, luoroscopyguided radiography, and computed tomography after TKA. The same baseline was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
6
25
0
Order By: Relevance
“…The medial and lateral joint surfaces of the knee joint were also used for the tibia. The present study showed that 3DCT measurement had excellent intra-and interclass reliability [14,15,18,29].…”
Section: Tablesupporting
confidence: 57%
See 4 more Smart Citations
“…The medial and lateral joint surfaces of the knee joint were also used for the tibia. The present study showed that 3DCT measurement had excellent intra-and interclass reliability [14,15,18,29].…”
Section: Tablesupporting
confidence: 57%
“…The postoperative femorotibial angle (FTA) was also measured as the leg axis between the anatomical axis of the femur and tibia in the coronal plane defined by the coordinate systems. The postoperative 3DCT images of the femur and tibia were superimposed onto those of the preoperative 3DCT plan using ZedView software (Figure 3) [14,15,18,19].…”
Section: Pre-and Postoperative Three-dimensional Computed Tomography Imagesmentioning
confidence: 99%
See 3 more Smart Citations